ANALISIS PEMANFATAAN BRAND AMBASSADOR DAN DIGITAL MARKETING TERHADAP KEPUTUSAN KONSUMEN DALAM UPAYA PEMBELIAN PRODUK DI TIKTOK - Viyang, Cyinthia Rachael; Tanjora, Berlian (POLITEKNIK LP3I JAKARTA, 2026)
The rapid growth of social media, particularly TikTok, has transformed digital marketing strategies and consumer purchasing behavior. This study aims to analyze the influence of brand ambassador utilization and digital marketing on consumer purchase decisions on the TikTok Shop platform. The theoretical framework is based on the concepts of brand ambassadors, digital marketing, and consumer purchase decisions from the perspectives of digital marketing and consumer behavior. This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire using a Likert scale, involving 106 active TikTok users who had made purchases through TikTok Shop. The data analysis techniques included validity and reliability testing, classical assumption tests, and multiple linear regression analysis using SPSS software. The results indicate that brand ambassadors and digital marketing have a positive and significant effect on consumer purchase decisions, both partially and simultaneously. Digital marketing demonstrates a more dominant influence compared to brand ambassadors. The coefficient of determination shows that a substantial proportion of the variation in purchase decisions can be explained by these two variables. This study concludes that the effective integration of brand ambassador strategies and digital marketing plays a crucial role in enhancing marketing effectiveness and encouraging consumer purchase decisions on TikTok Shop.